2021
DOI: 10.1891/jdnp-d-20-00048
|View full text |Cite
|
Sign up to set email alerts
|

Nursing Students' Perception Regarding Community Health Nursing Practical Modules Experience, at the Faculty of Nursing, Modern University for Technology and Information, Egypt

Abstract: BackgroundLearning depends not only upon how teachers have designed and structured their subjects and courses but also upon how their students perceive and understand this design and structure. Understanding student's level of perception with their clinical education forms a basis of determining the quality of nursing education.ObjectiveAssess nursing students' perception of their learning experience with community health nursing practical modules.MethodsCross-sectional descriptive study, the convenience sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
1
0
0
Order By: Relevance
“…This finding refers to that there is a gradual increase in the number of male nursing students and no longer be an exclusively female profession. This result is supported by Moselhy, (2021) [26] , who found in her Egyptian study among nursing students, that more than half of the study subjects were males. While this finding contradicted Ahmed et al, (2018) [27] , who found in their study a high percentage of nursing students were female.…”
Section: Discussionsupporting
confidence: 58%
“…This finding refers to that there is a gradual increase in the number of male nursing students and no longer be an exclusively female profession. This result is supported by Moselhy, (2021) [26] , who found in her Egyptian study among nursing students, that more than half of the study subjects were males. While this finding contradicted Ahmed et al, (2018) [27] , who found in their study a high percentage of nursing students were female.…”
Section: Discussionsupporting
confidence: 58%